Advances in drug development for targeted therapies for glioblastoma. Issue 5 (23rd May 2020) - Yan, Ge; Wang, Yunfu; Chen, Jincao; Zheng, Wenzhong; Liu, Changzhen; Chen, Shi; Wang, Lianrong; Luo, Jie; Li, Zhiqiang
Abstract: Glioblastoma is the most aggressive primary brain tumor in adults. The prognosis of patients with primary glioblastoma treated with the current standard of care, tumor resection followed by radiation therapy and auxiliary temozolomide, remains poor. Integrative genomic analyses have identified essential core signaling pathways and frequent genetic aberrations, which provide potential drug targets for glioblastoma treatment. Drugs against these therapeutic targets have been developed rapidly in recent years. Although some have shown promising effects on models in preclinical studies, many have shown only modest efficacy in clinical trials. New therapeutic strategies and potent drugs are urgently needed to improve the prognosis of patients with glioblastoma. The goal of this review is to summarize the current advances in drug development for targeted glioblastoma therapies and to reveal the major challenges encountered in clinical trials or treatment. This study will provide new perspectives for future studies of targeted therapeutic drug development and provide insights into the clinical treatment of glioblastoma.